(3CSGdjH GJNGP GdbQGQGJ GdEOGQjI GdaYGdI (B/s - (3LdOI, Sdje HWQSs ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2009)
(3GdeaGgje GdCSGSjI aj GdbQGQGJ GdEOGQjI,eaghe GdJQTjO,GdYdGbI Hjf GJNGP GdbQGQGJ hMd GdeTcdGJ,CSGdjH GJNGP GdbQGQGJ ,CfhGY GdbQGQGJ GdGOGQjI,OhQ GdSjGSI aj UfY GdbQGQGJ,GdGJUGdGJ hOhQgG aj GJNGP GdbQGQGJ,fXe OYe GdbQGQGJ hGdEOGQI GdGdcJQhfjI,GdEHOGY hGdGHJcGQ aj GJNGP GdbQGQGJ,eTGcd heYhbGJ GJNGP GdbQGQGJ aj GdOhd GdfGejIs
(3HHdjhZQGajG(B:(3U U (B.199-202s
Keywords: (3GJNGP GdbQGQGJs; (3GdEOGQI GdJfajPjIs